Sarcoptes sp. Infection in Turtledoves (Geopelia striata) at Banyuwangi - Rahmadani, Rahmadani; Kusnoto, Kusnoto; Yudhana, Aditya (Jurnal Medik Veteriner, 2021)
This study aimed to explain the case of ectoparasite infection and the life cycle of parasites in turtledoves (Geopelia striata). Sarcoptes sp. one of the ectoparasites belonging to the phylum Arthropods, the Arachnid class, and the order Acarina.Sarcoptes sp. can infect the skin of the host through direct contact with infected animals and the environment. Sarcoptes sp. infects by forming a lump under the skin and severe infection causes a crust to form on the skin and is accompanied by itching. Physical examination was carried out by means of inspection of the infected skin area. Subsequent examinations were carried out on the dead skin cells mixed with fresh manure macroscopically and microscopically. Macroscopic examination was done by observing the condition of the skin that is discraped. Microscopic examination using native examination. Based on the negative examination, it was found that there were Sarcoptes sp. mites on an objective microscope with a 40x magnification. Geopelia striata can be infected with Sarcoptes sp. through direct contact with sick animals. The incubation period of Sarcoptes sp. after infection from infected animals was 3-6 weeks.